Foreword - Lukács, János (Public Finance Quarterly, 2025)
More than 245 years ago on 1 January 1780, under the editorship of Mátyás Ráth, the first Hungarian-language newspaper, the Magyar Hírmondó, was published in Bratislava. In 1796 the first Hungarian-language economic journal, the Magyar Újság, was published in Vienna. The intellectual quality, image and ideological orientation of both newspapers were determined by the editors, Mátyás Ráth and Ferenc Pethe, who progressively broadened the horizons of Hungarian society, gave space to the ideas of the Enlightenment and advocated the need for economic and social development. Like the Financial Review, the journals published academic articles, debates, references to foreign examples, book reviews and reports.